A personal view of the early development of computational neuroscience in the USA - Moore, John W. (Frontiers in Computational Neuroscience, 2010)
In the half-century since the seminal Hodgkin-Huxley papers were published, computational neuroscience has become an established discipline, evolving from computer modeling of neurons to attempts to understand the computational functions of the brain. Here, I narrate my experience of the early steps and sense of excitement in this field, with its promise of rapid development, paralleling that of computers.